A model for overcoming cyberloafing through islamic spirituality in Private Universities - Nurali, Nurali; Kurniawan, Indra; Nafidah, Lina Nasihatun (ARKA INSTITUTE, 2025)
This study examines the moderating role of Islamic spirituality in the workplace on the influence between employee perceptions of organizational justice and job satisfaction on internet misuse at work (or cyberloafing). In this study, the research design was cross-sectional with a survey method. The required data were collected through questionnaires from 232 samples of employees working at private universities (PTS) in East Java. In order to test the research hypothesis, the variant-based structural equation modelling (VB-SEM) technique was used in this study with the help of SmartPLS 4.0. The model testing results showed that organizational justice significantly impacts job satisfaction, and consequently, job satisfaction significantly affects cyberloafing. In addition, organizational justice significantly influences cyberloafing, and finally, organizational justice can significantly influence cyberloafing through job satisfaction. Furthermore, Islamic spirituality at work moderates the impact of organizational justice and job satisfaction toward cyberloafing. These findings contribute to a better understanding of the influence of organizational justice and job satisfaction on cyberloafing and support controlling cyberloafing through Islamic spirituality in the workplace.